2003
DOI: 10.1210/en.2003-0495
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Activation by Low 17β-Estradiol Concentrations of the Na+/H+ Exchanger in Rat Aortic Smooth Muscle Cells: Physiopathological Implications

Abstract: Low physiological concentrations of 17beta-estradiol increased the intracellular pH of rat aortic smooth muscle cells by a rapid nongenomic mechanism. This effect was due to stimulation of the Na+/H+ exchanger activity, measured using the intracellular pH-sensitive fluorescent probe 2',7'-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein. The 17beta-estradiol gave rise to a bell-shaped dose response, with a maximum at 10-12 m and no significant effect at 10-9 m. The specificity of the effect was verified by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Within 5 min, E2 activates endothelial nitric oxide synthase (eNOS), promoting NO release in endothelial cells (Caulin-Glaser et al, 1997;Haynes et al, 2000;Wyckoff et al, 2001;Chambliss et al, 2005;Kim and Bender, 2005). Rapid E2-stimulated phospholipase (PL) Cdependent IP 3 production, calcium influx, and PKCa activation have been reported in cultured endometrial (Perret et al, 2001), granulosa (Morley et al, 1992), isolated duodenal (Picotto et al, 1999), liver derived HepG2 (Marino et al, 1998(Marino et al, , 2001c, and aortic smooth muscle (Incerpi et al, 2003) cells, as well as in the rat liver (Marino et al, 2001d). E2 rapidly stimulates the activation of MAPK pathways in neuroblastoma (Watters et al, 1997), pheochromocytoma (PC12) cells (Alexaki et al, 2006), mammary gland derived MCF-7 (Castoria et al, 1999;Lobenhofer et al, 2000;Castoria et al, 2001), endothelial Chambliss et al, , 2005, bone (Endoh et al, 1997;Jessop et al, 2001), and HepG2 cells .…”
Section: Rapid Membrane-initiated 17b-estradiol Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 5 min, E2 activates endothelial nitric oxide synthase (eNOS), promoting NO release in endothelial cells (Caulin-Glaser et al, 1997;Haynes et al, 2000;Wyckoff et al, 2001;Chambliss et al, 2005;Kim and Bender, 2005). Rapid E2-stimulated phospholipase (PL) Cdependent IP 3 production, calcium influx, and PKCa activation have been reported in cultured endometrial (Perret et al, 2001), granulosa (Morley et al, 1992), isolated duodenal (Picotto et al, 1999), liver derived HepG2 (Marino et al, 1998(Marino et al, , 2001c, and aortic smooth muscle (Incerpi et al, 2003) cells, as well as in the rat liver (Marino et al, 2001d). E2 rapidly stimulates the activation of MAPK pathways in neuroblastoma (Watters et al, 1997), pheochromocytoma (PC12) cells (Alexaki et al, 2006), mammary gland derived MCF-7 (Castoria et al, 1999;Lobenhofer et al, 2000;Castoria et al, 2001), endothelial Chambliss et al, , 2005, bone (Endoh et al, 1997;Jessop et al, 2001), and HepG2 cells .…”
Section: Rapid Membrane-initiated 17b-estradiol Effectsmentioning
confidence: 99%
“…Blood vessel walls consist of smooth muscle cells and an endothelial cell lining. In humans, both ERa and ERb are expressed in vascular endothelial cells and vascular smooth muscle cells (Mendelsohn, 2000;Incerpi et al, 2003). NO released by vascular endothelial cells induces relaxation of vascular smooth muscle and inhibits activation of platelets.…”
Section: Estrogen Receptors and Cardiovascular Diseasementioning
confidence: 99%
“…These rapid events may be classified into four main signaling cascade: phospholipase C (PLC)/protein kinase C (PKCs) [100][101][102][103][104][105][106], Ras/Raf/MAPK [72,[107][108][109][110][111][112][113], phosphatidyl inositol 3 kinase (PI3K)/AKT [15,16,80,81,97,[114][115][116][117][118], and cAMP/ protein kinase A (PKA) [104,[119][120][121][122][123].…”
Section: Estrogen Receptor Non-genomic Activ-itymentioning
confidence: 99%
“…The mechanism of this particular action of tetrac has not been established. While it is possible that the function of the P-glycoprotein is affected by crosstalk with the tetrac-occupied hormone receptor on the integrin, we have also suggested that the action of tetrac on the NHE may be involved (Incerpi et al, 2003). That is, inhibition of the NHE and a resultant intracellular decrease in pH may affect Pglycoprotein function because of the pH optimum of the MDR pump.…”
Section: Thyroid Hormone Stimulates Human Breast Cancer Cell Prolifermentioning
confidence: 84%
“…The integrin receptor for agonist thyroid hormone analogues and for tetrac, however, influences other local cell membrane events. For example, activity of the Na + /H + exchanger (NHE1) is regulated by thyroid hormone analogues and this action is blocked by tetrac (Incerpi et al, 2003). The insertion of Na, K-ATPase protein into the plasma membrane and activity of the ATPase (sodium pump) are also affected nongenomically by a MAPK-and PI3K-dependent mechanism (Lei et al, 2007).…”
Section: Thyroid Hormone Stimulates Human Breast Cancer Cell Prolifermentioning
confidence: 99%